Cognitive frailty and 5-year adverse health-related outcomes for the Malaysian elders longitudinal research (MELoR) study - Ong, Janice Ying Qian; Sumaiyah, Mat; Kioh, Sheng Hui; Kejal, Hasmuk; Nor'izzati, Saedon; Hazlina, Mahadzir; Chia, Ai-Vyrn; Shahrul, Bahyah Kamaruzzaman; Tan, Maw Pin * (Springer, 2022)
Purpose: To determine the risk of adverse outcomes among prefrail and frail individuals with and without cognitive impairment as well as those with isolated cognitive impairment compared to robust individuals without cognitive impairment.